Riverbank Erosion Using GIS and Remote Sensing Along the Greater Zab River in Iraq (Iraqi National Journal of Earth Science (INJES), 2026)
Studying the relationships between rivers and human activity is now crucial due to the significance of rivers for their morphology. The purpose of this study is to identify the historical human impacts on the Greater Zab River’s (GZR) morphology. To detect the GZR bank line and flow path and estimate the rate of erosion and sedimentation along the riverbank for the period from 1952 to 2023, a time series of satellite images and a single toposheet have been analyzed utilizing Arc GIS 10.8 software. The results reveal that between the 1950s and the 2020s, the GZR underwent significant narrowing, shortening, and embankment due to various human influences, climate changes, and geomorphological conditions as well. Sand mining, bank erosion and accumulation, together with Land Use/Land Cover (LULC) changes, are the main sources of the GZR's depletion and violent alteration of its propagation. The investigation also reveals that throughout the previous 7 decades, an area of around 9.38 km2 was eroded, with the highest erosion rate during the decade (1984 to 1993). The GZR was generally wider in 1952 than it would be in 2023 in the two periods' shifting regions. Throughout the years, it is also possible to observe a frequent change in the river courses. The conclusion of this study highlights the value of using a geospatial approach to effectively analyze riverbank erosion in alluvial channels.
Keywords: Environmental Degradation, River Erosion and Deposition, GIS, Remote Sensing.